The Chlorophyll Content Of Dalugha (Cyrtosperma merkusii (Hassk.) Schott) In Open & Shaded Light Conditions In The Swamp Edge Of Lake Kapeta, Siau Island, Sitaro Regency - Semuel P. Ratag; Euis F.S. Pangemanan (Jurnal Agroekoteknologi Terapan, 2023)
Plant chlorophyll plays an important role in the process of photosynthesis. The amount of its content in the leaves can indicate its adaptation to light conditions. This article describes the chlorophyll content of the Dalugha plant in the swamp edge of Lake Kapeta, Siau Island, Sitaro Regency which grows in open light, open-shaded and shaded conditions. This study aims to analyze the differences in the chlorophyll content of Dalugha plant leaves in open, open-shaded, and shaded growing conditions. The method used is an observational method in which the response of plants is observed in a range of conditions provided by nature. Chlorophyll content was observed by measuring the absorbance of plant leaf extracts using a spectrophotometer. The results showed that there were differences in chlorophyll content in the leaves of the Dalugha plant growing under open light, open-shaded, and shaded conditions. In open light conditions it is lower than in open-shaded and shaded conditions. Keywords: Dalugha, Chlorophyll, Light  Abstrak Klorofil tanaman berperan penting dalam proses fotosintesis. Jumlah kandungannya dalam daun bisa menunjukkan adaptasinya terhadap kondisi cahaya. Artikel ini menggambarkan tentang kandungan klorofil tanaman Dalugha di rawa tepi Danau Kapeta, Pulau Siau, Kabupaten Sitaro yang bertumbuh pada kondisi cahaya terbuka, terbuka-ternaungi, dan ternaungi.  Penelitian ini bertujuan untuk untuk menganalisis perbedaan kandungan klorofil daun tanaman Dalugha pada kondisi tempat tumbuh terbuka, terbuka-ternaungi, dan ternaungi. Metode yang digunakan adalah metode observasional dimana respon tanaman diamati pada suatu kisaran kondisi yang diadakan oleh alam. Kandungan klorofil diamati dengan metode pengukuran absorban ekstrak daun tanaman menggunakan spektrofotometer. Hasil penelitian menunjukkan bahwa ada perbedaan kandungan klorofil dalam daun tanaman Dalugha yang bertumbuh pada kondisi cahaya terbuka, terbuka-ternaung, dan ternaung. Pada kondisi cahaya terbuka lebih rendah dibandingkan pada kondisi terbuka-ternaung dan kondisi ternaung. Kata kunci: dalugha, klorofil, cahaya